2016
DOI: 10.1590/1414-431x20165215
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anti-OVA IgG2c production in vivo by enalapril

Abstract: Angiotensin-converting enzyme (ACE) inhibitors have non-hemodynamic, pleiotropic effects on the immune response. The effects of ACE inhibitors on the production of cytokines and T-cell functions are well established. However, little is known on the effects of these medicines on humoral response to foreign antigens. In this study, we investigated the effect of enalapril treatment on ovalbumin (OVA)-specific IgG1 and IgG2c production in mice determined by ELISA. Two groups of 8-week-old C57BL/6 females mice (3–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In an experimental model of infection with dengue virus, enalapril administration seemed to normalize the levels of IL-1beta and decreased the number of cells expressing viral antigen [58]. In diabetic nephropathy this medicament failed to modulate the B cell-mediated immune response [59], which is contradictory to the previously mentioned impact of enalapril on humoral immunity in healthy mice [55]. On the other hand, treatment with this drug may promote macrophage polarization towards the M1 phenotype [59].…”
Section: Enalaprilmentioning
confidence: 81%
See 2 more Smart Citations
“…In an experimental model of infection with dengue virus, enalapril administration seemed to normalize the levels of IL-1beta and decreased the number of cells expressing viral antigen [58]. In diabetic nephropathy this medicament failed to modulate the B cell-mediated immune response [59], which is contradictory to the previously mentioned impact of enalapril on humoral immunity in healthy mice [55]. On the other hand, treatment with this drug may promote macrophage polarization towards the M1 phenotype [59].…”
Section: Enalaprilmentioning
confidence: 81%
“…This drug impacts the humoral immunity as well. It has been shown that enalapril administration significantly increases the production of IgG2c without affecting IgG1 synthesis in mice immunized with ovalbumin [55]. However, enalapril-induced effects seem to depend on mouse sex, and thus likely on the activity of sex hormones, since this drug causes the reduction of production of pro-inflammatory IL-1α, protein-1 monocyte chemoattractant, and macrophage-1a protein in females, and increases the synthesis of anti-inflammatory cytokine IL-10 in males [56].…”
Section: Enalaprilmentioning
confidence: 99%
See 1 more Smart Citation
“…Research relating to ACE inhibition and immune impact is limited to cytokine production, adaptive immunity, and autoimmune diseases with conflicting evidence across multiple studies regarding immune advantage or disadvantage [ 78 ]. ACE and Ang II have increasing roles in mediating inflammation and altering immune cell populations as presented above.…”
Section: Discussionmentioning
confidence: 99%
“…Enalapril resulted in an increase in CD4 + T lymphocyte maturation and IL-10 production, with macrophage polarization shifted toward the M1 state. IgG1 production was unaffected by enalapril treatment; however, IgG2c levels were increased after 4 weeks in lupus-prone mice [ 78 ]. Whether these changes are Ang II-dependent or Ang II-independent is unknown and should be investigated further in the future by treating with ARBs in parallel.…”
Section: Arb and Acei: Effects On Immune Abilitiesmentioning
confidence: 99%